2015
DOI: 10.3390/su70912856
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Mitigation on Methane and Ammonia Production by Using Origanum vulgare L. and Rosmarinus officinalis L. Essential Oils on in Vitro Rumen Fermentation Systems

Abstract: Abstract:The effects of increasing concentrations of oregano (Origanum vulgare L.) and rosemary (Rosmarinus officinalis L.) essentials oil (EO) on ruminal gas emissions were tested in vitro using 50 mL serum bottles. Each bottle contained a 200 mg substrate (alfalfa hay and corn meal 1:1) and a 20 mL solution composed of a buffered medium and rumen fluid (1:2). The percentage of ruminal fermentation products was quantified by an infrared analyzer. The reduction of total gas production was 6% and 9% respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 43 publications
7
31
1
4
Order By: Relevance
“…The addition of OEO to cultures in the present study resulted in reductions in VFA concentration and total gas production suggesting that the fermentation and microbial activity were negatively impacted at the dose utilized in this study. These effects are consistent with the findings of others (Castillejos et al, 2006;Patra and Yu, 2012;Cobellis et al, 2015). In general, at high doses, OEO or its components decrease the fermentation and microbial activity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The addition of OEO to cultures in the present study resulted in reductions in VFA concentration and total gas production suggesting that the fermentation and microbial activity were negatively impacted at the dose utilized in this study. These effects are consistent with the findings of others (Castillejos et al, 2006;Patra and Yu, 2012;Cobellis et al, 2015). In general, at high doses, OEO or its components decrease the fermentation and microbial activity.…”
Section: Discussionsupporting
confidence: 92%
“…Busquet et al (2006) reported reductions in VFA concentration and CH4 production with high doses of OEO (300 and 3000 mg L 1 ) but not when included at 30 mg L 1 . Cobellis et al (2015) also observed similar reductions in VFA concentration when OEO was added to rumen cultures at high doses.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The latest estimates calculate the contribution of ruminants equal to 16–25 % to the total greenhouse gases emissions and EOs are recognized as safe a rumen modifier feed additive . Three works of Cobellis and collaborators draw a clear picture of the advantages and disadvantages of using secondary metabolites such as rumen modulators evaluating scientific production in recent years including essential oils. The authors concluded that if on one hand EOs may be promising natural substances to mitigate rumen methane production, improve rumen fermentations, and reduce environmental impact of ruminant production from the other side further research will be required to determine their active compounds/effective doses/mode of action, effect on organoleptic characteristics of animal products in order to evaluate a clear cost–benefit ratio prior to use them as additives at farm level.…”
Section: Essential Oils: Very Old ‘Guys’ With Great Prospectsmentioning
confidence: 99%
“…Venting the gas produced requires that CH 4 concentration is measured simultaneously, given that different CH 4 concentrations can be expected depending on substrate or stage of incubation. Although the most common method to measure CH 4 concentration on gas samples collected from incubation vessels is by using gas chromatography, as for in vivo measurements, other techniques are available and have been used such as infrared methane analysis (Goel et al, 2008;Cobellis et al, 2015) and absorption of CO 2 (Fievez et al, 2005).…”
Section: Incubation Procedures and Ch 4 Measurementsmentioning
confidence: 99%